Periprocedural hemodynamic depression is associated with a higher number of new ischemic brain lesions after stenting in the international carotid stenting study-MRI substudy - Altinbas, A; Algra, A; Bonati, L; Brown, M; Kappelle, L; De Borst, G; Hendrikse, J; Van Der Tweel, I; Van Der Worp, H (American Heart Association, 2013)
Background and Purpose— Carotid artery stenting (CAS) is associated with a higher risk of both hemodynamic depression and new ischemic brain lesions on diffusion-weighted imaging than carotid endarterectomy (CEA). We assessed whether the occurrence of hemodynamic depression is associated with these lesions in patients with symptomatic carotid stenosis treated by CAS or CEA in the randomized International Carotid Stenting Study (ICSS)-MRI substudy. Methods— The number and total volume of new ischemic lesions on diffusion-weighted imaging 1 to 3 days after CAS or CEA was measured in the ICSS-MRI substudy. Hemodynamic depression was defined as periprocedural bradycardia, asystole, or hypotension requiring treatment. The number of new ischemic lesions was the primary outcome measure. We calculated risk ratios and 95% confidence intervals per treatment with Poisson regression comparing the number of lesions in patients with or without hemodynamic depression. Results— A total of 229 patients were included (122 allocated CAS; 107 CEA). After CAS, patients with hemodynamic depression had a mean of 13 new diffusion-weighted imaging lesions, compared with a mean of 4 in those without hemodynamic depression (risk ratio, 3.36; 95% confidence interval, 1.73–6.50). The number of lesions after CEA was too small for reliable analysis. Lesion volumes did not differ between patients with or without hemodynamic depression. Conclusions— In patients treated by CAS, periprocedural hemodynamic depression is associated with an excess of new ischemic lesions on diffusion-weighted imaging. The findings support the hypothesis that hypoperfusion increases the susceptibility of the brain to embolism. Clinical Trial Registration— URL: http://www.controlled-trials.com. Unique identifier: ISRCTN25337470.